Kajian Sosiolinguistik Terhadap Istilah-istilah Pandemi Corona 2019 - Susy Deliani; Julia Lestari; Rizka Atika Putri; Nabilla Safitri; Inge Falderika; Novi Sri Wahyuni (Multiverse: Open Multidisciplinary Journal, 2022)
This study analyzes the relationship of social phenomena in society and the Indonesian language. Sociolinguistic studies in this case relate to the 2019 Corona Pandemic phenomenon that has hit the world, Indonesia has not been spared either. Events that have an impact, especially in the fields of health, the economy as well as language. The Indonesian language as a citizen of the global world language is also affected by this incident. Positively, the inclusion of new terms that are translated into Indonesian are immediately absorbed, as well as abbreviations and acronyms. This adds to the Indonesian treasury. The method of this research, descriptive qualitative. The data was obtained from online news and distribution from the government regarding the Covid-19 pandemic. The amount of data collected was 101 data. Then analyzed according to the category of the group. The results of this study found that there were 6 categories of the terms analyzed. With two dominant groups, namely: 1) Categories of Indonesian Words and Phrases with a high frequency of use and 2) Categories of Foreign Language Words and Phrases with a high frequency